Mode-hop-free tunable optical parametric oscillator utilizing a whispering gallery mode resonator - Förtsch, Michael; Schunk, Gerhard; Sedlmeir, Florian; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Schwefel, Harald G.L.; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
We report on a compact and stable optical parametric oscillator in a whispering gallery mode resonator, that combines very low pump thresholds with versatile tunability. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05